Proteomic Profile of Mabuya sp. (Squamata: Scincidae) Ovary and Placenta During Gestation. Issue 4 (11th April 2017) - Hernández‐Díaz, Nathaly; Torres, Rodrigo; Ramírez‐Pinilla, Martha Patricia
GRAPHICAL ABSTRACT: Proteins expressed during gestation were identified in ovarian and placental tissues in the viviparous placentotrophic lizard Mabuya sp. Most of the proteins expressed are highly conserved and might play a similar role to those proteins regulating gestation and growing in amniote embryos. ABSTRACT: Reptiles are one of the most diverse groups of vertebrates, providing an integrated system for comparative studies on metabolic, animal physiology, and developmental biology. However, the molecular data available are limited and only recently have started to call attention in the "omics" sciences. Mabuya sp. is a viviparous placentrotrophic skink with particular reproductive features, including microlecithal eggs, early luteolysis, prolonged gestation, and development of a highly specialized placenta. This placenta is responsible for respiratory exchange and the transference of all nutrients necessary for embryonic development. Our aim was to identify differentially expressed proteins in the ovary and placenta of Mabuya sp. during early, mid, and late gestation; their possible metabolic pathways; and biological processes. We carried out a comparative proteomic analysis during gestation in both tissues by sodium dodecyl sulfate polyacrylamide gel electrophoresis, two‐dimensional gel electrophoresis, and matrix‐assisted laser desorption/ionization. Differential protein expression in both tissues (Student's t‐test P < 0.05) was related to several processes such as cell structure, cell movement, and energy. Proteins found in ovary are mainly associated with follicular development and its regulation. In the placenta, particularly during mid and late gestation, protein expression is involved in nutrient metabolism, transport, protein synthesis, and embryonic development. This work provides new insights about the proteins expressed and their physiological mechanisms in Mabuya sp. placenta and ovary during gestation.